Suara Anak Negeri: Pelatihan Menulis Kreatif bagi Anggota Komunitas Literasi - Piliang, Wilda Srihastuty Handayani; Evadila, Evadila; Erni, Erni; Firdaus, Kennata Syaildani Hadi; Sari, Indah (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2026)
Creative writing training activities are a form of community service that aims to develop literacy skills, creativity, and intellectual capacity among the younger generation. The programme, entitled ‘Suara Anak Negeri: Creative Writing Training for Members of the Literacy Community’, was held on Monday, 2 June 2025, at the Fisabilillah Hall in the Riau Provincial Language Centre Building. The event was opened by the Head of the Riau Province Language Centre, Umi Kulsum, S.S., M.Hum., and featured a speaker, Listi Mora Rangkuti, S.S., M.Hum. The target audience for the event was members of the Riau Sastra Community, most of whom were students from various universities in Pekanbaru. The methods used in the event included training, writing practice, discussion, and mentoring. The results of the activity showed a significant improvement in the participants' writing skills, particularly in terms of idea exploration, diction selection, cohesion of ideas, and creativity. This activity also strengthened the network of productive and sustainable literacy communities in Riau Province. This programme made a significant contribution to strengthening creative literacy and fostering literary communities in Riau Province.